Role of Neutrophil Leukocytes in Cutaneous Infection Caused by Staphylococcus aureus - Mölne, Lena (American Society for Microbiology, 2000)
Despite the high prevalence of cutaneous infections, little is known about the role of host immune responsiveness during Staphylococcus aureus dermatitis. We have recently described a murine model of infectious dermatitis induced by superantigen-producing S. aureus. To assess the role of neutrophils in staphylococcal dermatitis, mice were given granulocyte-depleting monoclonal antibody prior to and on several occasions following intracutaneous inoculation with staphylococci. The granulocyte-depleted mice that had been intradermally inoculated with S. aureus developed crusted ulcerations which tended not to heal, whereas animals injected with control monoclonal antibody displayed only minor and transient skin lesions. The finding of severe ulcerations in neutropenic mice correlated with a significantly higher burden of bacteria in the blood and skin during the early phase of the infection. Importantly, while mice with an intact granulocyte population showed only limited skin infection, bacteremia occurred in the great majority of the neutrophil-depleted animals. As a consequence, the latter individuals exhibited significantly increased levels of the proinflammatory cytokine interleukin-6 and specific antibodies to staphylococcal cell wall components and toxic shock syndrome toxin-1 in the serum. Our data point to a crucial protective role of granulocytes in S. aureus dermatitis.